Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376296
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Necessity of Delay in Marking Menu Invocation

Abstract: Delayed display of menu items is a core design component of marking menus, arguably to prevent visual distraction and foster the use of mark mode. We investigate these assumptions, by contrasting the original marking menu design with immediately-displayed marking menus. In three controlled experiments, we fail to reveal obvious and systematic performance or usability advantages to using delay and mark mode. Only in very constrained settings-after significant training and only two items to learn-did traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Levels of annoyance ( Fig. 2-e) ranged from "Slightly-" (4) to "Extremely annoying" (5) with a majority of "Very annoying" (13). Finally, consequences were mostly "Minor" (Fig.…”
Section: Examples Of Interferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of annoyance ( Fig. 2-e) ranged from "Slightly-" (4) to "Extremely annoying" (5) with a majority of "Very annoying" (13). Finally, consequences were mostly "Minor" (Fig.…”
Section: Examples Of Interferencesmentioning
confidence: 99%
“…[10,32]), but also early on in HCI [23] wherein RT has become a frequent measure of interaction technique performance (see e.g. [13,17,22,25] for recent examples). Interaction interferences involve a specific type of reaction time, sometimes called "Stop-Signal Reaction Time" (SSRT), in which the stimulus calls for an absence of reaction, or for the inhibition of an already planned reaction.…”
Section: Interferences From the System's Perspectivementioning
confidence: 99%
“…However, as a rehearsal-based technique, FastTap uses a delay before displaying the menu. Delay not only can increase error rate [32,46] but also its necessity has been questioned in the context of Marking Menus [32]. On the other hand, SoftCuts is a delay-less technique that relies on a keyboard layout, a spatially consistent interface.…”
Section: Command Selection On Smartphones/tabletsmentioning
confidence: 99%
“…It offers both novice and expert modes of interaction, where for the latter, the menu only gets displayed after a delay. However, several studies have suggested that users have difficulties to adopt the expert mode [18,29] and a recent study also investigated the necessity of the delay-based appearance [21] of Marking Menus, hence raising similar questions for existing techniques, such as FastTap.…”
Section: Command Selection With Touch-based Devicesmentioning
confidence: 99%